STUDYING LINGUISTIC UNITS EXPRESSING EMOTIONS IN ENGLISH AND UZBEK LANGUAGES - Muxamadjonova Laylo; Yaqubjonova Rozixon (Ustozlar uchun, 2025)
Abstract: The study focuses on the lexical-semantic field of linguistic units expressing emotions in English and Uzbek, analyzing their structural composition and semantics. The research aims to compare these lexical-semantic fields in both languages, generalize their common features, and identify language-specific phenomena.